2018
DOI: 10.1016/j.clcc.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic Toxicity Occurring During Anti-EGFR Monoclonal Inhibitor Therapy in Patients With Metastatic Colorectal Cancer: A Systematic Review

Abstract: Monoclonal antibody inhibitors of the epidermal growth factor receptor (EGFR) have been shown to improve outcomes for patients with metastatic colorectal cancer (mCRC) without RAS gene mutations. However, treatment with anti-EGFR agents can be associated with toxicities of the skin, nails, hair, and eyes. Because these dermatologic toxicities can result in treatment discontinuation and affect patient quality of life, their management is an important focus when administering anti-EGFR monoclonal antibodies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 84 publications
3
50
0
Order By: Relevance
“…Rash is likely to occur, while pruritus and mucositis are less likely to be observed (21). Few patients had grade 3 skin-related toxicities (22). In phase I/II study of necitumumab, rash (70.5%), dry skin (18.2-67%), pruritus (11.4-60%), paronychia (36.4%) and grade ≥ 3 events, rash (20.5%) were observed (23,24).…”
Section: Common Appearances Involved In Anti-egfr Treatmentmentioning
confidence: 99%
“…Rash is likely to occur, while pruritus and mucositis are less likely to be observed (21). Few patients had grade 3 skin-related toxicities (22). In phase I/II study of necitumumab, rash (70.5%), dry skin (18.2-67%), pruritus (11.4-60%), paronychia (36.4%) and grade ≥ 3 events, rash (20.5%) were observed (23,24).…”
Section: Common Appearances Involved In Anti-egfr Treatmentmentioning
confidence: 99%
“…DEBIOC is also the first study to consider AZD8931 in long-term postsurgical maintenance therapy, during which time 58% patients experienced AZD8931-related AEs, the most common being skin rash. Although skin rash is a common grade IIIeIV toxicity typically occurring in 10e20% of patients receiving tyrosine kinase inhibitors [29], no events of this nature grade III were observed with AZD8931 in the expansion phase. The discordance between the diagnostic biopsy and resection specimens for both HER2 and EGFR status, demonstrates potential heterogeneity of expression in these cancers or indeed a neoadjuvant treatment effect.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study with patients undergoing oral chemotherapy reported that many patients feel helpless at home when they do not have enough information and knowledge about their treatment and symptoms [7]. In general, education on the self-management of dAEs is recommended both before and after initiation of cancer therapy [4, 5, 17, 18]. However, it is difficult for patients to predict the disease outlook because various types of dAEs may develop [1, 18], and exacerbation and improvement of symptoms often repeatedly occur after the initiation of EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Proper management is essential to minimize patient discomfort during cancer therapy [4, 5]. Although there are no standard therapies for targeted therapy-induced dAEs, treatments, such as skin moisturizers and topical ointments, have been recommended to prevent and reduce the symptoms [6].…”
Section: Introductionmentioning
confidence: 99%